Groundwater Microbiology of an Urban Open‐Loop Ground Source Heat Pump with High Methane. Issue 2 (15th February 2023) - J. Barnett, Megan; J. Farr, Gareth; Shen, Jianxun; Gregory, Simon
Abstract: Ground source heat pumps (GSHPs) are low‐carbon alternatives to gas boilers for decarbonizing heating. Open‐loop GSHP systems abstract groundwater, pass it through a heat exchanger, and return it to ground or surface water. Groundwater samples from the top and base of an abstraction and a recharge borehole of an open‐loop GSHP system in Cardiff, UK were assessed, and compared to two local boreholes in the same aquifer. Groundwater samples were taken when the GSHP system was active (once) and inactive (twice) and analyzed for changes in geochemistry, viable cell counts, and microbial community (16S rRNA gene sequencing). The GSHP had a distinct geochemistry and microbial community compared to the control boreholes, and the abstraction borehole showed greater variability than the recharge borehole. The microbial community of the GSHP system showed an increase in relative abundance of genera involved in oxidation of methane and methylated compounds, of which Methylotenera was the most abundant (up to 83.9% of 16S rRNA gene sequences). There were also changes in genera associated with nitrification ( Nitrospira, Nitrosomonas ) and those with potential for sulfur and iron cycling ( Rhodoferax ). Methane concentration was analyzed after identification of methylotrophs and found that methane concentrations were up to 2855 μg L −1, thus likely having had a significant impact on the bacterial communities present. Understanding the microbiology and biogeochemistry of GSHP systems provides insight into potential issues with local infrastructure and long‐term system performance, and supports modeling to maximize efficient and sustainable use of the subsurface. Abstract : Article impact statement : Open‐loop ground source heat pumps influence biogeochemical carbon, nitrogen, and sulfur cycles and alter bacterial communities.